Leadership and power - Kessler, V. (Koers, 2010)
Leadership does not exist without power. Thus we have to reflect on power in order to lay a theoretical foundation for responsible leadership. This interdisciplinary article collects insights from the disciplines of theology, sociology, and crosscultural management. It provides a concise summary of what a Christian leader should know about power in order to use his/her power in an adequate way. The theological reflection reminds us of the fact that, according to the Judeo-Christian tradition, God gave power to humankind (Guardini, 1998). Two opposite dangers are described in this article, namely the abuse of power on the one hand and the misconception of powerlessness as a Christian virtue on the other hand. The sociological section describes different forms of power. Following French and Raven (1960), it introduces seven power bases, which are illustrated by examples from society and the church. The next section describes the different cultural perceptions on power. It shows how the cultural parameter of power distance may influence the appropriate leadership style (Hofstede & Hofstede, 2005). It is argued that our understanding of a right or wrong use of power is strongly influenced by the culture in which we grew up. The article concludes with a list of ethical guidelines on the use of power for responsible Christian leaders.